SMART BUBBLES LAUNDRY: THE IMPLEMENTATION OF INDUSTRY ON CAMPUS APPROACH IN SUNGAI PETANI COMMUNITY COLLEGE: Industry On Campus - Rahman, Reezlin (Advances in Social Sciences Research Journal, 2021)
This conceptual paper was developed to illustrate the planning and implementation of the Industry on Campus (IOC) at Sungai Petani Community College. In general, the IOC was designed based on the basic concepts developed by the Department of Education Polytechnic and Community College, Ministry of Higher Education Malaysia. The IOC's implementation at the Sungai Petani Community College was implemented through the one of the SPCC Niche Area, which is Laundry service in the cluster of Hotel Operation. The IOC in Sungai Petani Community College involves collaboration with the industries; D’Kota Resources and MD Chan Enterprise is a form of strategic collaboration to develop high-skilled human resources from the institution to the industries. All the efforts and commitments in regards to the IOC approach at Smart Bubble Laundry have been reported in this paper as a pilot project documentation for the new education concept for TVET education. It is hoped that companies' and institutions' continuous efforts will contribute to high marketability workers, the national economy, and the community's social life.